Contested Construction of Roma Identity: “Copycat Roma” versus the Authentic Roma / Roman Kimliğinin Çatışmalı İnşası: “Fotokopi Romanlık” Karşısında Otantik Romanlık - Ozan Uştuk (Folklor/Edebiyat, 2021)
Roma identity and representation are quite controversial both in academia and among Roma people themselves. The cultural identity of Roma, which primarily foregrounds ethnic constituency, is constructed through the boundary work between the Roma and the Other (Gadjo, non-Roma people). The heterogeneous nature of the Roma identity indicates that it is a contested identity construction process. Examining the effects of intragroup conflicts, which have a significant impact on the establishment of cultural identity, is possible through in-depth and long-term ethnographic research that goes beyond depicting culture as a monolithic discursive repertoire. In this study, the critical ethnographic method has been adopted, which allows us to focus on intragroup conflicts among the Roma people along with the diversity of the representations produced by Roma-Gadjo intercultural communication. Through critical ethnography, the heterogeneous and fragmented cultural structure produced by cultural negotiation and conflict regarding what “authentic” or “real” Roma should be, has been examined. It is done by listening to the points of view and voices of the subjects. Thus, without denying the historical experiences and the potential agency of the research subjects, this study examines how the specific identity representations of the Roma have positioned in hegemonic discourses.